Penilaian ciri fiziko-kimia tanih pasir di persekitaran dataran banjir Sg. Langat, Selangor untuk penanaman rumput dan pertanian - Sahibin Abd. Rahim,; Wan Mohd. Razi Idris,; Zulfahmi Ali Rahman,; Tukimat Lihan,; Ramlan Omar,; Shahrul Rizal Ahmad, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
Study on physico-chemical characteristics of sandy soil developed on flood plain of Sg. Langat was carried out. Three soil sampling stations (S1, S2 and S3) were selected to collect the soil to be tested. Physico-chemical characteristics determined were pH, electrical conductivity, organic matter content, size distribution, soil density, water retention potential and evaporation potential. pH was determined in soil: water ration of 1:2.5, whereas electrical conductivity was determined in saturated gypsum extract. Size distribution was determined by pippette method together with dry sieving. Hydraulic conductivity was measured using falling head method. Density and porosity were calculated and water retention was determined by freely draining saturated soil to achieve field capacity. Evaporation was measured through daily decreased in soil weight. Values of soil pH ranged from 4.93 to 5.57, whereas electrical conductivity was below 3.4 mS.cm-1. Soil was dominated by very fine sand and fine sand particle size with their respective content in S1, S2 and S3 of 28.5, 29.5 and 25.0%, and 38.1, 23.2 and 24.2%. High sand content in the soil rendered the water held by sand particles at low suction from -0.19 to -1.67 bar. Bulk density of soil was moderate and organic matter content was very low (<1). Porosity of soil was around 55%. Water content at field capacity was between 51 hingga 59%, whereas air contents were between 41 to 49%. Based on these characteristics grasses as well as other crops planted on this soil would experience low water availability if watering is not carried out constantly